Refining the prize: Chinese oil refineries and its energy security. Issue 3 (26th May 2016) - Kim, Inwook
Abstract: Since China became a net oil importer in 1993, oil refineries have played integral roles in China's quest for oil security. And yet, the capacity, security, and configurations of refineries were rarely featured in the discussions about China's oil policy. To fill this gap, this paper explains the basics of refinery economics and technology, and details the development in China's refining industry since the early 1990s. By taking refineries into consideration, it then revisits and reassesses the existing literature regarding the motives and drivers behind China's foreign oil policy, its effectiveness, and the political interactions between China and crude oil producers.